2003
DOI: 10.1161/01.hyp.0000086201.27420.33
|View full text |Cite
|
Sign up to set email alerts
|

Training-Induced, Pressure-Lowering Effect in SHR

Abstract: Abstract-We showed that the training-induced, pressure-lowering effect correlates with decreased arteriole wall/lumen ratio and venule growth in the gracilis muscle. To investigate whether these beneficial changes are tissue-specific or occur in other muscles and tissues, we analyzed the effects of hypertension and training on microcirculatory profile of locomotor/nonlocomotor muscles and another nonmuscular tissue. Spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats were submitted to low-intensity tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
3
18

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 30 publications
10
96
3
18
Order By: Relevance
“…Indeed, Moreno et al (27) reported a high kidney weight in female hypertensive rats (vs normotensive controls), which could be a useful "intermediate phenotype" of hypertension. These observations agree with pressure measurements obtained by us and by others: male SHR had higher pressure levels than female SHR (range of 170-185 vs 150-160 mmHg for males and females, respectively) (22,25,26). In general, sex differences have not been extensively explored, since most of the studies were done with male animals.…”
Section: Mechanisms Conditioning Cardiovascular Changes In Hypertensionsupporting
confidence: 91%
See 3 more Smart Citations
“…Indeed, Moreno et al (27) reported a high kidney weight in female hypertensive rats (vs normotensive controls), which could be a useful "intermediate phenotype" of hypertension. These observations agree with pressure measurements obtained by us and by others: male SHR had higher pressure levels than female SHR (range of 170-185 vs 150-160 mmHg for males and females, respectively) (22,25,26). In general, sex differences have not been extensively explored, since most of the studies were done with male animals.…”
Section: Mechanisms Conditioning Cardiovascular Changes In Hypertensionsupporting
confidence: 91%
“…In spontaneously hypertensive rats (SHR), the best known experimental model for essential or primary hypertension in humans, we confirmed that high blood pressure levels are accompanied by remodeling of arterioles (increased wall-to-lumen ratio) and capillary rarefaction in many tissues including the skeletal muscles, in which we demonstrated a normal resting blood flow, besides the altered vascular structure (22)(23)(24)(25)(26). According to Mulvany (16), vascular remodeling in hypertension is characterized by increased wall-to-lumen ratio of arteries and arterioles, being classified as eutrophic (decrease in both lumen and outer diameter, with unaltered wall thickness or cross-sectional area) or hypertrophic (increase in media thickening, that encroaches on the lumen).…”
Section: Mechanisms Conditioning Cardiovascular Changes In Hypertensionsupporting
confidence: 65%
See 2 more Smart Citations
“…People who can maintain a regular regimen of activity that is of longer duration or of more vigorous intensity are likely to derive greater health benefits than individuals who lead sedentary lives of physical inactivity which is considered to be the strongest individual risk factor for poor health (63). Exercise and lifestyle changes as therapeutic interventions for successfully managing symptoms of hypertension have been found to be efficacious in previous controlled studies (32, 41,44,69,70,71). For instance, aerobic exercise can be valuable in the treatment of mild to moderate essential hypertension because it may cause a decrease in both SBP and DBP.…”
Section: Discussionmentioning
confidence: 99%